Assessment of training need and training efficacy for national program for prevention and control of cancer, diabetes, cardiovascular diseases and stroke among medical officers of West Bengal, India - Saha, Indrajit; Mitra, Satabdi; Chatterjee, Ananta; Mukhopadhyay, Jyotishman; Chatterjee, Chitra (International Journal Of Community Medicine And Public Health, 2019)
Background: The national program for prevention and control of cancer, diabetes, cardiovascular diseases and stroke (NPCDCS) has been rolled out in West Bengal, with its implementation initiated through state-wide training of Medical Officers (M.O). For attaining requisite competency for meeting NPCDCS objectives, MOs have been trained at their respective district levels. Present study aimed to assess the training need, training efficacy and need for further training. Methods: A repeat cross-sectional study was conducted from May-July 2018 for M.Os of six randomly chosen districts of West Bengal, out of those whereat NPCDCS was launched in first phase. 40-45 M.Os were randomly selected from each district in liaison with district level health authorities. The total sample size was 352 with Finite population correction. On the days of training, pre and post training surveys were conducted with an identical semi-structured, pre-tested and validated questionnaire (Cronbach’s alpha >0.8) covering different levels of cognitive domain, with a maximum possible score of 100 marks. No negative marking was done for incorrect responses. Training was imparted by the Principal Investigator (accredited trainer). Ethical clearance was granted by the State Health Directorate. Informed consent from each participant was obtained. Results: Dependent sample t-test revealed significant increment (p<0.0001) in post-test scores (t=63.134) & one-way repeated measure general linear model (GLM) also revealed F=29.617 (p<.0001). The “Effect Size” was classified as “Huge” (Cohen’s D=63.134/√(352)= 3.365), as was noted between pre-test and post-test scores, based on Cohen’s convention and Sawilowsky’s addition. It was further noted that even after six hour training sessions there was 27.44% knowledge gap (p<0.0001) after adjusting for Bonferroni. Conclusions: Imperativeness of training coupled with periodic refresher training has been established as a pre-requisite for successful implementation of NPCDCS.